Financial and economic factors affecting foreign direct investment - a panel estimation study of the ASEAN-5 countries / Geetha Subramaniam ... [et al.] - Subramaniam, Geetha; Rasiah, Ratneswary; Selvaratnam, Doris Padmini; Ramachandran, Jayalakshmy (Universiti Teknologi MARA, 2021)
ASEAN's strength stems from its diversity, which generates a plethora of diverse market opportunities. Over the last few decades, Foreign Direct Investment (FDI) has risen significantly as a major source of international capital transfer, but the COVID-19 pandemic had a detrimental effect on FDI flows, with the outlook for ASEAN remaining highly unpredictable and contingent on the length of the crisis, the efficacy of policy efforts to encourage investment and to mitigate the economic consequences of the pandemic. This study examines the long-run relationships and shortrun dynamic interactions between FDI and its determinants comprising of market size, trade openness, stock market capitalisation and financial development over the period 1970 to 2019. The study applies the dynamic heterogeneous panel estimation techniques of Mean Group (MG), Pooled Mean Group (PMG) and Dynamic Fixed Effects (DFE) to analyse a set of macro panel data of the ASEAN-5 countries, to establish the possible relationships between these variables. An analysis of the results reveals the existence of a long-run causality between FDI and its predictors, indicated by the significant error correction terms for the models tested in this study. There is evidence that market size and stock market capitalization significantly contribute to FDI, with market size being the most dominant contributor. Interestingly, the study also reveals that trade openness and financial development are not significant in determining FDI in the selected countries. The study concludes with an examination of policy implications and also sheds some light on the outlook of FDI in ASEAN-5 post Covid 19.